Spacecraft systems engineering - Fortescue, Peter W.; Stark, John; Swinerd, Graham (J. Wiley, 2003)
Introduction - The spacecraft environment and its effect on design - Dynamics of spacecraft - Celestial mechanics - Mission analysis - Propulsion systems - Launch vehicles - Spacecraft structures - Attitude control - Electrical power systems - Thermal control of spacecraft - Tele-communications - Telemetry, command, data handling and processing - Graound stations - Spacecraft mechanisms - Spacecraft electromagnetic compatibility engineering - Product assurance - Small-satellite engineering and application - Spacecraft system engineering.